GROWTH OF FOUR FAST GROWING TREE SPECIES ON TAILINGS MEDIA FROM GOLD MINING COMPANY PT ANTAM UBPE PONGKOR - Ulfah J Siregar; Wirrahma . (Jurnal Silvikultur Tropika, 2016)
Tailing from mining activity contains heavy metal that can be managed by phytoremediation. Plant selection to be used in phytoremediation plays important role that determine the success of these activities. The objective of this research is to study the growth of four forest tree species in media containing tailings from gold mining. Four fast growing tree species, i.e. Swietenia macrophylla King., Anthocephalus macrophyllus (Roxb.) Havil., Maesopsis eminii Engl., and Toona sureni (Blume) Merr., and two kinds of growing media, i.e. tailings and mixture of tailings + compost with 3:1 ratio, were used in a Completely Randomized Factorial Design. The growth parameters measured were plant height and diameter, leaf length and width, number of leaves, stomata density, total wet and dry biomass, also root-shoot ratio, and percentage of survival. The results of the research showed that plant types significantly affect all parameters observed. Media treatment had significant effect on total wet and dry biomass only. Interaction between plant types and media gave significant effect only on total wet biomass. Based on survival and growth parameter observed A. macrophyllus gave best performance.Key words: A. macrophyllus, M. eminii, phytoremediation, S. macrophylla, tailings, T. sureni